Assessing investment priorities for inclusive agricultural transformation in Tanzania - Aragie, Emerta A.; Benfica, Rui; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James (Wiley, 2024)
Policy‐makers dealing with conflicting development goals and constrained budgets must comprehend the relative cost effectiveness of agricultural and rural development initiatives.We assess the impact of alternative interventions on development outcomes—economic growth, job creation, poverty reduction, and diet quality—to inform decision‐making and resource allocation in Tanzania's agriculture. We analyse trade‐offs among development objectives and explore budget reallocation to enhance the efficiency of public spending.We used a computable general equilibrium (CGE) model linked top‐down with microsimulation modules to simulate the impact of public investment options.No single option emerges as the most effective across all development objectives. Investments in improved inputs and extension for horticulture and cash crops stand out for diet quality and employment creation. Livestock services show consistently high rankings across multiple objectives. Investments to boost cereals and root crops promote growth and reduce poverty but do little to increase employment and diet quality.Budget reallocation towards more cost‐effective interventions can significantly enhance the development effectiveness of Tanzania's agricultural expenditures and would substantially increase cumulative gross domestic product growth between 2019 and 2028.Policy‐makers can use the findings to design and prioritize agricultural interventions that better align with broader development objectives. Tanzania can achieve higher benefits and contribute to overall development goals by reallocating resources towards more cost‐effective expenditure options.